An analysis of the ability to take a rapid step forward, concerns about falling and balance in a group of older people with osteoporosis – a cross sectional study. (3rd April 2018) - Thorberg, Maria; Ståhle, Agneta; Halvarsson, Alexandra
Abstract: Purpose: To describe the ability to take a rapid step forward, and to investigate the relationship between a rapid step forward, concerns about falling (CAF) and balance performance. Materials and methods: A cross-sectional study including 96 elderly people, aged 66–87, with osteoporosis and fear of falling. The ability to take a rapid step forward (step execution) under single- (ST) and dual-task (DT) conditions was measured, as were CAF (Falls Efficacy Scale International (FES-I)) and balance performance (MFE). Results: A step executed during DT takes significantly longer than during ST ( p  < .001). Significant differences for step execution during both ST ( p  = .007) and DT ( p  = .005) were observed when comparing participants with low CAF (FES-I < 22) and high CAF (FES-I > 23). There was a moderate correlation between balance performance and step execution ( rs  = 0.54) for ST and a low correlation ( rs  = 0.39) for DT. Little, if any correlation was found between CAF (FES-I) and step execution ( rs  = 0.13–0.19). Conclusion: It takes significantly longer for elderly with osteoporosis and fear of falling to execute a rapid step forward during DT than during ST. Moreover, it takes significantly longer to execute a step forward during both ST and DT for elderly people with high CAF compared to those with low CAF.